2011
DOI: 10.4236/jmp.2011.22011
|View full text |Cite
|
Sign up to set email alerts
|

Natural Convective Boundary Layer Flow over a Horizontal Plate Embedded in a Porous Medium Saturated with a Nanofluid

Abstract: A boundary layer analysis is presented for the natural convection past a horizontal plate in a porous medium saturated with a nano fluid. Numerical results for friction factor, surface heat transfer rate and mass transfer rate have been presented for parametric variations of the buoyancy ratio parameter Nr, Brownian motion parameter Nb, thermophoresis parameter Nt and Lewis number Le. The dependency of the friction factor, surface heat transfer rate (Nusselt number) and mass transfer rate on these parameters h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(55 citation statements)
references
References 15 publications
4
49
0
Order By: Relevance
“…Numerical computations are done for −1 ≤ f w ≤ 1, 0 ≤ N b ≤ 1, 0 ≤ N t ≤ 0.3, 0 ≤ Nr ≤ 0.2, 0.1 ≤ γ ≤ 5.0 and 0.1 ≤ Le ≤ 5.0. The results of the dimensionless heat transfer rates, −θ (0), and the dimensionless nanoparticle volume fraction rate, −φ (0) are compared with the most recent results reported by Gorla and Chamkha (2011) for a special case in Table 1 and are found to be in excellent agreement for each values of Nr, N b, and N t. This supports the validity of our other graphical results for dimensionless velocity, temperature, nanoparticle volume fraction, skin friction, heat, and nanoparticle volume fraction transfer rates.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Numerical computations are done for −1 ≤ f w ≤ 1, 0 ≤ N b ≤ 1, 0 ≤ N t ≤ 0.3, 0 ≤ Nr ≤ 0.2, 0.1 ≤ γ ≤ 5.0 and 0.1 ≤ Le ≤ 5.0. The results of the dimensionless heat transfer rates, −θ (0), and the dimensionless nanoparticle volume fraction rate, −φ (0) are compared with the most recent results reported by Gorla and Chamkha (2011) for a special case in Table 1 and are found to be in excellent agreement for each values of Nr, N b, and N t. This supports the validity of our other graphical results for dimensionless velocity, temperature, nanoparticle volume fraction, skin friction, heat, and nanoparticle volume fraction transfer rates.…”
Section: Resultsmentioning
confidence: 97%
“…2a displays the effects of buoyancy ratio and suction parameter on the dimensionless velocity when thermophoresis and the Brownian motion parameters are absent. It is found that the dimensionless velocity and corresponding velocity boundary Table 1 Comparison of results if this study with Gorla and Chamkha (2011) for different values of buoyancy and nanofluid parameters Present results Gorla and Chamkha (2011) Fig. 2b displays the effects of buoyancy ratio and suction parameter on the dimensionless velocity when thermophoresis and the Brownian motion parameters are present.…”
Section: Velocity Profilesmentioning
confidence: 94%
See 2 more Smart Citations
“…Nield and Kuznetsov [16] investigated the cross-diffusion in nanofluids, with the aim of making a detailed comparison with regular cross diffusion effects and the cross-diffusion effects peculiar to nanofluids, and at the same time investigating the interaction between these effects when the base fluid of the nanofluid is itself a binary fluid such as salty water. Recently, a boundary layer analysis for the natural convection past a horizontal plate in a porous medium saturated with a nanofluid is analyzed by Gorla and Chamkha [17].…”
Section: Introductionmentioning
confidence: 99%